Relative condition factor and hematology of pacu breeders Piaractus mesopotamicus (Holmberg, 1887) (Research, Society and Development, 2020)
The objective of this study was studied relative condition factor and hematological parameters of males and females of pacu Piaractus mesopotamicus were after the process of hormonal induction and spawning. Field research was carried out, with quantitative and qualitative measures in which thirty healthy fish were randomly collected, 14 females and 16 males. A blood collection was then carried out to analyze the following parameters: hematocrit, total plasma protein, number of erythrocytes, hemoglobin, hematimetric indices, mean corpuscular volume (MCV) and mean corpuscular hemoglobin (MCHC) concentration. Total and differential leukocyte and thrombocyte count and plasma glucose were also determined. The condition factor was similar for both sexes, with values close to 1. The total plasma protein and the number of circulating neutrophils were higher in females (P